Commodity Prices and Exchange Rate Volatility : Lessons from South Africa's Capital Account Liberalization - Dumitrescu, Elena (IMF Working Papers; Working Paper ;, 2012)
We examine the relationship between South African Rand and gold price volatility using monthly data for the period 1980-2010. Our main findings is that prior to capital account liberalization the causality runs from South African Rand to gold price volatility but the causality runs the other way around for the post-liberalization period. These findings suggest that gold price volatility plays a key role in explaining both the excessive exchange rate volatility and current disproportionate share of speculative (short-run) inflows that South Africa has been coping with since the opening up of its capital account.